2011
DOI: 10.1111/j.1469-0691.2010.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and predictors of treatment failure in early post-surgical prosthetic joint infections due to Staphylococcus aureus treated with debridement

Abstract: Experience with debridement and prosthesis retention in early prosthetic joint infections (PJI) due to Staphylococcus aureus is scarce. The present study aimed to evaluate the outcome and predictors of failure. Patients prospectively registered with an early PJI due to S. aureus and 2 years of follow-up were reviewed. Demographics, co-morbidity, type of implant, clinical manifestations, surgical treatment, antimicrobial therapy and outcome were recorded. Remission was defined when the patient had no symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
106
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 21 publications
11
106
1
2
Order By: Relevance
“…However, the number of patients with MRSA PJI remaining at risk after treatment was very small, so it is difficult to know whether the rate of failure after treatment of these individuals would not also be significant. Other studies using combination therapy with rifampin and fluoroquinolone for S. aureus PJI have reported short-term treatment success rates ranging from 62 to 75% (355,369), compared to a rate of 36% in an older study without rifampin (127). The short-term treatment success rate may be up to 80% when rifampin combination therapy is used in properly selected patients (125).…”
Section: Debridement With Prosthesis Retentionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the number of patients with MRSA PJI remaining at risk after treatment was very small, so it is difficult to know whether the rate of failure after treatment of these individuals would not also be significant. Other studies using combination therapy with rifampin and fluoroquinolone for S. aureus PJI have reported short-term treatment success rates ranging from 62 to 75% (355,369), compared to a rate of 36% in an older study without rifampin (127). The short-term treatment success rate may be up to 80% when rifampin combination therapy is used in properly selected patients (125).…”
Section: Debridement With Prosthesis Retentionmentioning
confidence: 93%
“…The longer duration of oral combination therapy is predicated on the often larger amount of soft tissue infection in knee arthroplasty infections. Some clinicians use a fluoroquinolone combined with rifampin even during the initial phase of therapy (63,355,369), a practice supported by both IDSA and International Consensus Meeting documents (60,251). This has not been directly compared to the use of an initial period of intravenous antimicrobials.…”
Section: Debridement With Prosthesis Retentionmentioning
confidence: 99%
“…In the last 15 years, the combination of rifampin with other antibiotics (e.g., fluoroquinolones) has demonstrated a 70 to 90% success rate (1,3,11,21). Failure has been associated with at least one of the following: (i) the type of isolated microorganism (16), mainly methicillin-resistant staphylococci and enterococci, (ii) the need for more than 1 debridement to control the infection, (iii) a high C-reactive protein concentration at the moment of diagnosis (21), and (iv) the antibiotic or combination of antibiotics administered (5). The management of patients who fail while they are on treatment has not yet been well-defined.…”
mentioning
confidence: 99%
“…However, the purpose of the present study was to evaluate only studies reporting on hip joint infections. Several well-designed studies with a higher level of evidence report about DAIR including both THA and total knee arthroplasty (TKA) cases, whereas a differentiation of the results between both primary surgeries is not possible [15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Similar to that, other studies present data only about small case series [29][30][31] .…”
mentioning
confidence: 99%
“…Some authors recommend a duration of antibiotic treatment for 6 mo for TKA-PJIs and 3 mo for THA-PJIs when treated with DAIR [4] . In some recent studies, it has been reported that a shorter course of antibiotics might be also an alternative in DAIR treatment [21,23,28,37] . This confusion regarding the optimal duration of antibiotic therapy is also evident in the present literature review.…”
mentioning
confidence: 99%